Lower Bound Capacity of Strip Footings on Rock Masses with Two Discontinuity Sets - Widjojo Adi Prakoso (Himpunan Ahli Teknik Tanah Indonesia, 2022)
This paper presents a lower bound model for predicting the rock strip footing bearing capacity. The model is based on strip footings on rock masses with two sets of ubiquitous, closed discontinuities. The model considers explicitly the strength of the intact rock and the discontinuities, as well as the number and orientation of the discontinuities. The validation of the model is presented. The parametric study of footings on rock masses with two discontinuity sets having the same strength is performed, and the results are reported graphically in detail. The bearing capacity is controlled primarily by the rock structures (number of discontinuity sets and orientation) and the discontinuity strength, and it is controlled by the intact rock strength for a very limited number of cases. The minimum bearing capacity factor is independent of the intact rock friction angle, but it is a linear function of discontinuity cohesion. The bearing capacity factor is also presented in terms of its ratio to UCS; the ratio for the maximum bearing capacity is rather insignificantly affected by intact rock friction angle, and not linearly correlated to discontinuity cohesion. The bearing capacity factor for rock masses with low discontinuity strengths tends to be more sensitive to any variation in discontinuity orientation. There are some exceptions to the above points, suggesting that there would always be some rock mass conditions leading to unexpected rock footing bearing capacities and therefore good characterization processes of rock masses would always be essential. The practical significant of this study is briefly discussed.